PENDIDIKAN ANAK USIA DINI PERSFEKTIF ISLAM DAN BARAT (Studi Pustaka Tentang Teori PAUD) - rosita rosita; ahmad buchori muslim (Al-Mudarris: Journal Of Education, 2019)
This library research was conducted with a background of enriching discourse and paradigm regarding the pattern of Early Childhood Education (PAUD) in Islamic and Western perspectives. In addition, researchers want to detect and see the pioneer of PAUD theory. Because there are some similarities from the originators of western theory with the Islamic PAUD theory. Although there are different things between the two perspectives. One of them, the western perspective reveals the beginning of the right AUD education since the womb, but vice versa with AUD education in the Islamic perspective, that is, starting from choosing a partner. So that the idea of this research arises by using a literature analysis. Thus, this research is expected to provide a new positive discourse and have a purpose to provide an actual understanding of what is happening around us.